Literature Review: Peranan Media Informasi Kesehatan Dalam Penanganan Kasus KLB (Covid 19) - Willy Haposan; Deasy Rosmala Dewi; Noor Yulia; Wiwik Viatiningsih (Yayasan Literasi Sains Indonesia, 2022)
The number of deaths due to Covid-19 is increasing from time to time. The industrial era 4.0 is one of the eras of public information disclosure, therefore there are many media that can be used to support communication patterns and activities. This information disclosure will make it easier for citizens to carry out remote control and communication to monitor activities carried out by the government in dealing with this pandemic. This is one form of easy access to public information disclosure supported by information technology media. The purpose of this study was to determine the role of health information media in controlling the COVID-19 outbreak and to find out the most common way the media used to provide health information on Covid-19. This study was designed using a Literature review that examines the Role of Information Media in Handling Covid-19 cases. The results of a study of 8 journals found that health information media had several roles in handling Covid 19. The largest role was the media that played a role in educating the public about the importance of implementing health protocols and social distancing. It can be concluded that the role of the information media in handling the Covid-19 outbreak is very important, because the media are asked to always update data quickly, validly and in real time. The media are also asked to be able to break the chain of spread of Covid-19 by informing the travel ban, recommendations to comply with health protocols and recommendations to comply with social distancing procedures. distancing is the most common way.